Práxis pedagógica na filosofia de paulo freire: : um estudo dos estádios da consciência - Correia, Wilson (2020)
The present article assumes as subject the study of the direction of the praxis pedagogical in Pablo Freire and it makes it by means of the inquiry of the direction of the levels of conscience and brief exposition on the trajectory freireana bibliographical-professional. The study it follows the rules of the bibliographical research and if it abides by the analytical and synthetic reading of specialized literature. Objective to evidence that, currently, the task of the professor and the teacher would have to consist of developing one practical professor whom it aims at to the reach of the critical conscience on the part of the same apprenticees and itself. It concludes affirming that, in the assistance society as the Brazilian, practical politics directed toward the affirmation of the anti-criticism make with that the faculty be it a true challenge reason for which valley the penalty to undertake it.